Effect of BRCA2 sequence variants predicted to disrupt exonic splice enhancers on BRCA2 transcripts - Brewster Brooke L; Pettigrew Christopher A; Whiley Phillip J; Walker Logan C; Spurdle Amanda B; Brown Melissa A (BMC, 2010)
Abstract Background Genetic screening of breast cancer patients and their families have identified a number of variants of unknown clinical significance in the breast cancer susceptibility genes, BRCA1 and BRCA2. Evaluation of such unclassified variants may be assisted by web-based bioinformatic prediction tools, although accurate prediction of aberrant splicing by unclassified variants affecting exonic splice enhancers (ESEs) remains a challenge. Methods This study used a combination of RT-PCR analysis and splicing reporter minigene assays to assess five unclassified variants in the BRCA2 gene that we had previously predicted to disrupt an ESE using bioinformatic approaches. Results Analysis of BRCA2 c.8308 G > A (p.Ala2770Thr) by mRNA analysis, and BRCA2 c.8962A > G (p.Ser2988Gly), BRCA2 c.8972G > A (p.Arg2991His), BRCA2 c.9172A > G (p.Ser3058Gly), and BRCA2 c.9213G > T (p.Glu3071Asp) by a minigene assay, revealed no evidence for aberrant splicing. Conclusions These results illustrate the need for improved methods for predicting functional ESEs and the potential consequences of sequence variants contained therein.